Non‐invasive monitoring of branched Au nanoparticle‐mediated photothermal ablation. Issue 8 (13th August 2016) - Zhao, Ken; Cho, Soojeong; Procissi, Daniel; Larson, Andrew C.; Kim, Dong‐Hyun
Abstract: Nanoparticle‐mediated photothermal therapy for treatment of different types of tumors has attracted tremendous attention in recent years. One major factor that drives this therapy is the ability to carefully control and prevent inadvertent damage to local tissues, while focusing therapeutic heating to specific regions of the tumor tissues. To this end, it is critical to generate efficient heating in the targeted tumors while monitoring the extent and distribution of heating. In our study, we demonstrated the photothermal heating properties of our synthesized branched Au nanoparticles (b‐AuNPs) using non‐invasive MR thermometry (MRT) techniques to assess its effects both in vitro and in vivo . 75 nm b‐AuNPs were synthesized; these b‐AuNPs demonstrated strong near infrared (NIR) absorption and high heat transducing efficiency. Proton resonance frequency MRT approaches for monitoring b‐AuNPs mediated heating were validated using in vitro agar phantoms and further evaluated during in vivo animal model tumor ablation studies. In vitro phantom studies demonstrated a strong linear correlation between MRT and reference‐standard thermocouple measurements of b‐AuNPs‐mediated heating upon NIR laser irradiation; temperatures increased with both an increase in laser power and increased exposure duration. Localized photothermal heating in regions containing the b‐AuNPs was confirmed through MRT generated temperature maps acquired serially at increasing depths during both phantom and in vivo studies. Our results suggested that b‐AuNPs exposed to NIR radiation produced highly efficient localized heating that can be accurately monitored dynamically using non‐invasive MRT measurements. © 2016 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 105B: 2352–2359, 2017.